Prevention of Deep Vein Thrombosis after Hip Replacement - Planès, André; Samama, Meyer M.; Lensing, Anthonie W. A.; Büller, Harry R.; Barre, Jeanne; Vochelle, Nicole; Beau, Bertrand (Thrombosis and Haemostasis, 1999)
Consecutive patients undergoing total hip replacement in 43 centres were randomly assigned to receive blindly either enoxaparin (40 mg) or tinzaparin (4,500 anti-Factor IU Xa), as once daily subcutaneous injections. The first injection was administered 12 h preoperatively. Efficacy was assessed by bilateral venography performed 12-14 days postoperatively. Efficacy and safety were blindly and centrally adjudicated. Among the 499 patients included, 440 had a venogram. The total incidence of DVTs was 44 (20.1%) of the 219 patients of the enoxaparin group and 48 (21.7%) of the 221 patients of the tinzaparin group. The upper limit of the 80% confidence interval of the difference between the two treatment groups was less than 5.0%. Therefore according to the protocol’s specifications equivalence was shown. Proximal DVTs occurred in 10.5% of the enoxaparin group (23 patients) and in 9.5% (21 patients) of the tinzaparin group. No overt major bleeding was observed. One patient in the enoxaparin group developed severe thrombocytopenia and died. The LMWH tinzaparin appears clinically to be as effective and safe as enoxaparin in the prophylaxis of deep vein thrombosis after total hip replacement, at the doses used and under the conditions of this study.